Tinjauan Yuridis Pengaturan Tindak Pidana Terhadap Kejahatan Benda Virtual dalam Game Online - Ida Ayu Putri Ary Yulandari; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Warmadewa Press, 2021)
Such rapid progress in the field of Information Technology has an impact on the patterns and aspects of people's lives which along with the progress of the times color the formation of new rules. Crimes and other crimes have actually developed, one of which is virtual object crime in online games. The purpose of this study is to reveal the legal regulation of criminal acts against virtual object crimes in online games and criminal sanctions against virtual object crimes from the perspective of ius constituendum. The research method used is the type of normative research. Sources of data used are primary, secondary and tertiary legal sources. The technique of collecting law is done by recording techniques deductively and inductively. After the data is collected then it is analyzed by means of legal interpretation. The results of the study revealed that the perpetrator committed a criminal act of fraud with the object of a virtual object crime, this is certainly contrary to the laws and regulations. Article 28 paragraph (1) of the ITE Law and Article 378 of the Criminal Code are references in resolving crimes against virtual objects in online games and the sanctions are Article 45 paragraph (2) of the ITE Law. The regulations that will be made can provide a deterrent effect and minimize virtual object crimes in Online Games.